2009
DOI: 10.1128/mcb.00338-09
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 1 Delta Regulates the Pace of the Mammalian Circadian Clock

Abstract: Both casein kinase 1 delta (CK1␦) and epsilon (CK1) phosphorylate core clock proteins of the mammalian circadian oscillator. To assess the roles of CK1␦ and CK1 in the circadian clock mechanism, we generated mice in which the genes encoding these proteins (Csnk1d and Csnk1e, respectively) could be disrupted using the Cre-loxP system. Cre-mediated excision of the floxed exon 2 from Csnk1d led to in-frame splicing and production of a deletion mutant protein (CK1␦ ⌬2 ). This product is nonfunctional. Mice homozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
192
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(221 citation statements)
references
References 40 publications
26
192
2
Order By: Relevance
“…In vitro studies in mammalian cell lines and tissues have also implicated both isoforms in setting the period of circadian oscillations (16,18,19), but the lethality of the CK1δ-null mutation has precluded an examination of their specific contributions to behaviorally relevant pacemaking in vivo. Our data now show that selective pharmacological suppression of the activity of CK1δ dose-dependently lengthens the period of circadian behavioral rhythms in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies in mammalian cell lines and tissues have also implicated both isoforms in setting the period of circadian oscillations (16,18,19), but the lethality of the CK1δ-null mutation has precluded an examination of their specific contributions to behaviorally relevant pacemaking in vivo. Our data now show that selective pharmacological suppression of the activity of CK1δ dose-dependently lengthens the period of circadian behavioral rhythms in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may reflect the contrasting molecular contexts of acute pharmacological inactivation of an existing enzyme and a genetic deletion where the protein is absent throughout development and tissue is potentially subject to developmental compensatory changes. Indeed, Etchegaray et al (18) showed that CK1ε is overexpressed in Ck1δ −/− liver and vice versa. Unlike genetic deletion, acute pharmacological inactivation also results in a catalytically inactive protein that nonetheless remains to perform other roles (e.g., complex formation, target protein binding).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CK1δ and CK1ε phosphorylate core clock proteins and trigger their degradation (Etchegaray et al, 2009). …”
Section: Casein Kinasesmentioning
confidence: 99%
“…Interestingly, the CK1 family shows a strong preference both in vitro and in vivo for 'primed,' pre-phosphorylated substrates (Cheong & Virshup 2011). Considering the broad distribution of CK1 family members and their substrates, these kinases have been found to participate in many biological activities, such as Wnt signaling (Peters et al 1999;Price 2006), biological rhythm (Etchegaray et al 2009;Lee et al 2009), DNA repair (Dhillon & Hoekstra 1994), and the cell cycle (Behrend et al 2000;Petronczki et al 2006). The Arabidopsis thaliana genome was found to contain 14 casein kinase 1-like (CKL) genes, and, within the conserved kinase domains, they share 89% sequence similarity at the aa level.…”
Section: Introductionmentioning
confidence: 99%